PENGARUH KEPEMIMPINAN DAN DISIPL PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PT. PLN (PERSERO) UNIT PELAKSANAAN PELAYANAN PELANGGAN TERNATE - Kurniawan Kodja; Abdullah W. Jabid; Zulkifli , (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The objectives of this study were: To determine the effect of leadership and work discipline on employee performance at PT. PLN (Persero) Ternate Customer Service Implementation Unit. The number of samples in this study were 55 employees of PT. PLN (Persero) UP3 Ternate. The test tool used is multiple linear regression analysis (multiple regression) using the statistical package for social scientists (SPSS) 23 as a statistical test tool. The results showed that: simultaneous testing of the influence of leadership and work discipline variables together had a significant effect on employee performance variables at PT. PLN (Persero) Ternate Customer Service Implementation Unit.